Functional inhibition of MEF2 by C/EBP is a possible mechanism of leukemia development by CEBP‐IGH fusion gene. Issue 3 (27th November 2022) - Odaira, Koya; Yasuda, Takahiko; Okada, Kentaro; Shimooka, Takuya; Kojima, Yukino; Noura, Mina; Tamura, Shogo; Kurahashi, Shingo; Iwamoto, Eisuke; Sanada, Masashi; Matsumura, Itaru; Miyazaki, Yasushi; et al.
Abstract: CEBPA‐IGH, a fusion gene of the immunoglobulin heavy‐chain locus ( IGH ) and the CCAAT enhancer‐binding protein α ( C/EBPα ) gene, is recurrently found in B‐ALL cases and causes aberrant expression of C/EBPα, a master regulator of granulocyte differentiation, in B cells. Forced expression of C/EBPα in B cells was reported to cause loss of B‐cell identity due to the inhibition of Pax5, a master regulator of B‐cell differentiation; however, it is not known whether the same mechanism is applicable for B‐ALL development by CEBPA‐IGH . It is known that a full‐length isoform of C/EBPα, p42, promotes myeloid differentiation, whereas its N‐terminal truncated isoform, p30, inhibits myeloid differentiation through the inhibition of p42; however, the differential role between p42 and p30 in ALL development has not been clarified. In the present study, we examined the effect of the expression of p42 and p30 in B cells by performing RNA‐seq of mRNA from LCL stably transfected with p42 or p30. Unexpectedly, suppression of PAX5 target genes was barely observed. Instead, both isoforms suppressed the target genes of MEF2 family members (MEF2s), other regulators of B‐cell differentiation. Similarly, MEF2s target genes rather than PAX5 target genes were suppressed in CEBP‐IGH ‐positive ALL ( n  = 8) compared with other B‐ALL ( n  = 315). Furthermore, binding of both isoforms to MEF2s target genes and the reduction of surrounding histone acetylation were observed in ChIP‐qPCR. Our data suggest that the inhibition of MEF2s by C/EBPα plays a role in the development of CEBPA‐IGH ‐positive ALL and that both isoforms work co‐operatively to achieve it. Abstract : In the present study, we found that C/EBPα aberrantly expressed in B cells inhibited the function of MEF2 family members by performing RNA‐seq of mRNA of C/EBPα‐transfectants and analyzing RNA‐seq data of 323 clinical samples of ALL. Two isoforms of C/EBPα, p42 and p30, co‐operatively worked for MEF2 inhibition, although it was reported that they worked competitively in AML development.